Synaptosomal and mitochondrial oxidative damage followed by behavioral impairments in streptozotocin induced diabetes mellitus: restoration by Malvastrum tricuspidatum - Solanki, I.; Parihar, P.; Shetty, R.; Parihar, M. S. (Cellular and Molecular Biology, 2017)
Synaptosomal and mitochondrial impairments in the brain of diabetic individual manifest metabolic risk factors that most likely affect the brain functions. Diabetes is associated with the structural and functional alterations of the brain and neuronal loss leading to cognitive and other behavioral impairments, thus reducing the quality of life. The biochemical mechanisms underlying the diabetes-associated behavioral decline are poorly understood. In the present study, we examined the effects of hyperglycemia on the oxidative stress and behavioral functions in streptozotocin-induced diabetic mice. Our results showed the increase in oxidative stress in synaptosomes and brain mitochondria marked by an increase in lipid peroxidation and protein carbonyl content and decline in reduced glutathione in mice treated with streptozotocin. The oxidative damage in synaptosomes and brain mitochondria further caused impairment in locomotor and memory behavioral functions. Furthermore, we examined the protective effects of plant extract derived from Malvastrum tricuspidatum against STZ induced oxidative stress and behavioural impairments. For the first time we showed that this plant extract attenuate synaptosomal and mitochondrial oxidative stress and behavioral impairments in mice treated with streptozotocin. We suggest that streptozotocin caused impairments in synaptosomes and brain mitochondria and altered behavioral functions via increase in the oxidative stress and decrease in the antioxidant defense system. These impairments in synaptosomes and brain mitochondria and alterations in behavioral functions are significantly prevented by supplementation of Malvastrum tricuspidatum extract.